2010
DOI: 10.21608/jfds.2010.82094
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Use of Some Natural Extracts as Anti- Fungi to Prolong the Conservation of Wheat and Its Products.

Abstract: Different extracts of carrot seeds, leaves, and roots were evaluated for their effectiveness inhibition on some groups of microorganism fungal growth and reducing the production of aflatoxins. Ethanol, Chloroform, and water showed effects against some groups of microorganisms which contaminated wheat products. Water and chloroform extracts of yellow carrot leaves showed the most effect against feacal group. Water, ethanol and chloroform extracts from carrot seeds, leaves, and root reduced the fungal growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…From Table ( 14), it could be observed that cake samples containing 9 to 15% banana peels powder (BPP) showed their free of mold and yeast until 6 days of storage, while the mold and yeast growth appeared at the lower substituted cakes with banana peels powder (BPP), (3 and 6%) and control sample after 6-12 days of storage. These results are agree with Emara et al (2010) who evaluated for their banana peels powder (BPP) effectiveness inhibition on some groups of microorganisms growth, these finding may be related to the comparative high natural antioxidants content and antioxidants activity in (BPP).…”
Section: -Microbiological Qualitysupporting
confidence: 91%
“…From Table ( 14), it could be observed that cake samples containing 9 to 15% banana peels powder (BPP) showed their free of mold and yeast until 6 days of storage, while the mold and yeast growth appeared at the lower substituted cakes with banana peels powder (BPP), (3 and 6%) and control sample after 6-12 days of storage. These results are agree with Emara et al (2010) who evaluated for their banana peels powder (BPP) effectiveness inhibition on some groups of microorganisms growth, these finding may be related to the comparative high natural antioxidants content and antioxidants activity in (BPP).…”
Section: -Microbiological Qualitysupporting
confidence: 91%
“…Water, ethanol and chloroform extracts from carrot seeds, leaves and root reduced the fungal growth rate. No aflatoxin was produced by fungi in wheat samples treated by extracts of carrot seeds, leaves and roots (Emara et al, 2010). El-Shehawy et al (2010) reported that total phenolic compounds (as gallic acid) of black berries leaves methanolic extract was 100.54 mg/ml.…”
Section: Introductionmentioning
confidence: 99%